Total quality management - Evans, James R.; Lindsay, William M. (Andover, Mass. : Cengage Learning Asia Pte Ltd, 2013)
This edition of quality control and management continues to embrace the fundamental principles and historical foundations of total quality and to promote high-performance management practices that are reflected in the Bladridge Criteria, while providing a foundation for understanding and applying Six Sigma.
Preface -- Part 1 The quality system -- Chapter 1 Introduction to quality -- Chapter 2 Philosophies and frameworks -- Chapter 3 Total quality in organizations -- Part 2 The management system -- Chapter 4 Focusing on customers -- Chapter 5 Process management -- Chapter 6 Performance measurement and strategic information management -- Chapter 7 Building and sustaining performance excellence in organizations -- Part 3 Six sigma and the technical system -- Chapter 8 Principles of six sigma -- Chapter 9 Design for six sigma -- Chapter 10. Tools for process improvement -- Appendixes
Keywords: TOTAL QUALITY MANAGEMENT